New Advances in Marine Engineering Geology - Xiaolei Liu; Qing Yang; Yin Wang; Dong-Sheng Jeng; Hendrik Sturm (Journal of Marine Science and Engineering, 2021)
The ocean is the cradle of life and is rich in natural resources [...]